Hubungan Spiritualitas dengan Kesepian pada Lansia di UPT Pelayanan Sosial Tresna Werdha (PSTW) - Ulfi Bini’Matillah; Latifa Aini Susumaningrum; Muhammad Zulfatul A`la (Pustaka Kesehatan, 2018)
Elderly is a condition where someone experience a lot of changes, for instance psychological change.Loneliness is a elderly psychological disorder elderly that can be overcome with spirituality. This studyaimed to analyze the correlation between spirituality and loneliness in elderly in the Pelayanan SosialTresna Werdha (PSTW) Jember. This research applied an observasional analytic design with crosssectional approach. 91 respondents are gained by employing simple random sampling using SpiritualWell-Being Scale (SWBS)(r=0,895) and UCLA Loneliness Scale (r=0,94). Data were analyzed byusing Spearmen correlation test with significance level of 0.05. The result of the spirituality variablereserach shows 71,00 median and ± 45-86, meanwhile on loneliness variable 38,00 median and ± 20-69. There was a significant negative correlation between spirituality ang loneliness (p value: 0.000 ; r:-0,718). Spirituality become one of coping strategy to overcome elderly’s loneliness. Spiritualitybecome power to elderly in facing problem and increasing life quality so can decrease their loneliness.The study shows that the importance of increasing the spirituality to decrease loneliness level onelderly who live at Panti Werdha.Keywords: elderly, spirituality, loneliness